The frequency of ingested plastic debris and its effects on body condition of short-tailed shearwater (Puffinus tenuirostris) pre-fledging chicks in Tasmania, Australia - Cousin, HR; Heidi Auman; Alderman, R; Patti Virtue (2015)
In recent years, there have been increasing reports of ingestion of marine plastic debris in seabirds. Our aim was to assess the frequency and effects of ingested plastic debris in pre-fledging Short-tailed Shearwaters ( Puffinus tenuirostris ) in Tasmania. We conducted necropsies of 171 Shearwater chicks, confiscated after illegal poaching, to determine the presence of plastic debris in the proventriculus and ventriculus. We also examined whether there was a correlation between body condition (based on body mass and fat-scores) and quantity of plastic ingested (by count and weight). We recorded 1032 ingested plastic particles, consisting of industrial plastic (31%) and user plastic (69%). Most of the Shearwater chicks (96%) contained plastic debris with a mean of 148.1 mgper bird (s.e. 8.1). Most plastic was found in the ventriculus. Light-coloured plastic dominated (63.8%), with the rest medium (22.1%) and dark (14.1%) plastics. We found that total mass of ingested plastic was not significantly related to body condition, or fat-scores or mass individually. Our study highlights the prevalence of plastic pollution in apparently healthy Shearwater chicks and underscores concern regarding the effects of increasing marine pollution on a global scale.